(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, a simple integration of differential-difference problem with singular perturbed nature using non polynomial interpolating function is presented. Firstly, an equivalent first-order problem of the given second order singularly perturbed equation. Resulting first order problem is solved by numerical integration using the non polynomial interpolating function. To analyse the method computationally, several model experiments have been solved and results are compared with upwind method for different values for the advanced, delay and the perturbation parameter. The cause of the small parameters on the layer solutions are presented in graphs.